PENGARUH PENGGUNAAN MULTIREPRESENTASI PADA PEMBELAJARAN BIOLOGI TERHADAP KETERAMPILAN KOMUNIKASI ABAD 21 PESERTA DIDIK - Azkiya Annurbaiti, - (2023)
This research purpose is to analyze the effect of using multirepresentation in biology learning on students' 21st century communication skill. This study was also conducted to reveal students' responses to the use of multirepresentation in biology learning. Biology learning often refers to memorizing concepts without paying attention to another assessment which are equally important in 21st century learning. The hypothesis of this study is there is an effect of using multirepresentations in biology learning on students' 21st century communication skills. The research method is pre-experimental with a descriptive quantitative approach. The research subjects were 32 students in one science class at one Bandung public high school selected by purposive sampling. Data was collected with a written communication skills test instrument, peer assessment sheet related to oral communication skills, and a response questionnaire as a supporting data source. The results showed that students' written communication skills before being given treatment were in the less skilled category with an average value of all indicators of 42.97% and increased after being given treatment to be quite skilled with an average value of all indicators of 68.23%. Students' oral communication skills at the first and second meeting were included in the skilled category. In general, students consider the use of multirepresentation helps them understand and communicate a concept. The implication of this research is that the use of multirepresentation in biology learning improves 21st century communication skill, especially in communicating effectively in diverse environments.